2021
DOI: 10.1007/s11837-021-05029-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Properties of Parts Fabricated with Gas- and Water-Atomized 304L Stainless Steel Powder in the Laser Powder Bed Fusion Process

Abstract: The use of gas-atomized powder as the feedstock material for the laser powder bed fusion (LPBF) process is common in the additive manufacturing (AM) community. Although gas-atomization produces powder with high sphericity, its relatively expensive production cost is a downside for application in AM processes. Water atomization of powder may overcome this limitation due to its low cost relative to the gas-atomization process. In this work, gas-and water-atomized 304L stainless steel powders were morphologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As for mechanical performance, the YS and UTS of the 316L stainless steel parts printed by the water-atomized powders are slightly lower than that of the gas-atomized powders, but the difference in the elongation and hardness is marginal [96,97]. Similarly, the YS (470 MPa), UTS (674 MPa), and elongation (29%) of the 304L stainless steel samples based on the water-atomized powders are lower than those of the gas-atomized counterparts (YS of 507 MPa, UTS of 688 MPa, and elongation of 69%) [100]. In contrast, Cacace and Semeraro [99] found that the mechanical properties were comparable for L-PBF samples printed with gas-atomized and water-atomized 316L stainless steel powders.…”
Section: Wamentioning
confidence: 88%
See 1 more Smart Citation
“…As for mechanical performance, the YS and UTS of the 316L stainless steel parts printed by the water-atomized powders are slightly lower than that of the gas-atomized powders, but the difference in the elongation and hardness is marginal [96,97]. Similarly, the YS (470 MPa), UTS (674 MPa), and elongation (29%) of the 304L stainless steel samples based on the water-atomized powders are lower than those of the gas-atomized counterparts (YS of 507 MPa, UTS of 688 MPa, and elongation of 69%) [100]. In contrast, Cacace and Semeraro [99] found that the mechanical properties were comparable for L-PBF samples printed with gas-atomized and water-atomized 316L stainless steel powders.…”
Section: Wamentioning
confidence: 88%
“…In this section, the preparation principles, advantages, and limitations of the above-mentioned powder preparation methods are described in turn. In addition, the mechanical properties of L-PBF parts with powders fabricated via different preparation methods are also compared, including the Ti6Al4V powders prepared by GA, EIGA, PA, and PREP [81][82][83][84][85][86][87][88][89], AlSi10Mg powders prepared by GA and PA [20,[90][91][92][93], Inconel 718 powders produced by GA and PREP [94,95], 316L stainless steel powders fabricated by GA, VIGA, and WA [96][97][98][99], and 304L stainless steel powders yielded by GA and WA [100].…”
Section: Powder Preparation Methodsmentioning
confidence: 99%
“…The ease of manufacture of components produced by Fused Deposition Modeling (FDM) out of Polymers makes them useful for rapid prototyping and scale testing of mechanisms and structures before mass-production or large-scale installation [21,22]. In addition, considering the process impacts on both user-safety and the environment, the lament format of feedstock material to FDM process is less hazardous than the other formats of feedstock, such as powder in powder-based AM processes [23][24][25][26]. Before the advent of affordable FDM technology, prototypes may have been manufactured out of polymers using injection molding, which is both timeconsuming and expensive on smaller scales [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The powder feedstock needs to have su cient owability in order to ensure that the powder adequately spreads along the build plate during the EB-PBF process. The more spherical particle geometries result in better owability and powder packing which consequently increases the powder bed density and improves the properties of fabricated parts [34][35][36][37]. Therefore, the powder feedstock to the EB-PBF process is recommended to be provided in spherical geometries.…”
Section: Introductionmentioning
confidence: 99%